Non-alcoholic Fatty Liver Disease (NAFLD), Type 2 Diabetes, and Non-viral Hepatocarcinoma: Pathophysiological Mechanisms and New Therapeutic Strategies - Erica Vetrano; Luca Rinaldi; Andrea Mormone; Chiara Giorgione; Raffaele Galiero; Alfredo Caturano; Riccardo Nevola; Raffaele Marfella; Ferdinando Carlo Sasso (Biomedicines, 2023)
In recent years, the incidence of non-viral hepatocellular carcinoma (HCC) has increased dramatically, which is probably related to the increased prevalence of metabolic syndrome, together with obesity and type 2 diabetes mellitus (T2DM). Several epidemiological studies have established the association between T2DM and the incidence of HCC and have demonstrated the role of diabetes mellitus as an independent risk factor for the development of HCC. The pathophysiological mechanisms underlying the development of Non-alcoholic fatty liver disease (NAFLD) and its progression to Non-alcoholic steatohepatitis (NASH) and cirrhosis are various and involve pro-inflammatory agents, oxidative stress, apoptosis, adipokines, JNK-1 activation, increased IGF-1 activity, immunomodulation, and alteration of the gut microbiota. Moreover, these mechanisms are thought to play a significant role in the development of NAFLD-related hepatocellular carcinoma. Early diagnosis and the timely correction of risk factors are essential to prevent the onset of liver fibrosis and HCC. The purpose of this review is to summarize the current evidence on the association among obesity, NASH/NAFLD, T2DM, and HCC, with an emphasis on clinical impact. In addition, we will examine the main mechanisms underlying this complex relationship, and the promising strategies that have recently emerged for these diseases’ treatments.